2015
DOI: 10.3389/fncel.2015.00049
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of Ca2+ signaling in astrocytic endfeet in the latent phase of temporal lobe epilepsy

Abstract: Astrocytic endfeet are specialized cell compartments whose important homeostatic roles depend on their enrichment of water and ion channels anchored by the dystrophin associated protein complex (DAPC). This protein complex is known to disassemble in patients with mesial temporal lobe epilepsy and in the latent phase of experimental epilepsies. The mechanistic underpinning of this disassembly is an obvious target of future therapies, but remains unresolved. Here we show in a kainate model of temporal lobe epile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
(53 reference statements)
2
11
0
Order By: Relevance
“…Prior research has also shown that activation of mGluR5, an astrocyte surface receptor, can serve as an upstream mediator of cell death following experimentally induced SE (Ding et al, 2007). Expression or functional activity of mGluR5 on astrocytes has been reported in five other models of epileptogenesis (Aronica et al, 2000; Ding et al, 2007; Ferraguti et al, 2001; Szokol et al, 2015; Ulas et al, 2000), with the low-dose, systemic KA mouse model representing the sixth model to date. The expression of mGluR5 on the mature astrocyte may be considered a feature of pathology, considering the expression of mGluR5 on astrocytes is limited to the first weeks of development in rodents (Morel et al, 2014; Sun et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…Prior research has also shown that activation of mGluR5, an astrocyte surface receptor, can serve as an upstream mediator of cell death following experimentally induced SE (Ding et al, 2007). Expression or functional activity of mGluR5 on astrocytes has been reported in five other models of epileptogenesis (Aronica et al, 2000; Ding et al, 2007; Ferraguti et al, 2001; Szokol et al, 2015; Ulas et al, 2000), with the low-dose, systemic KA mouse model representing the sixth model to date. The expression of mGluR5 on the mature astrocyte may be considered a feature of pathology, considering the expression of mGluR5 on astrocytes is limited to the first weeks of development in rodents (Morel et al, 2014; Sun et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…Neuronal activity induced elevations in astrocytic intracellular calcium levels may in turn facilitate astrocytic release of neuroactive substances including glutamate, aggravating epileptic activity [81]. In acute stages of epileptogenesis, calcium transients in astrocytes are increased, possibly contributing to elevated extracellular potassium levels via Calcium-dependent protease induced cleavage of the dystrophin associated protein complex [82, 83]. Elevated extracellular potassium levels in turn may lead to increased excitability of neurons and thereby generate epileptiform activity [84].…”
Section: Discussionmentioning
confidence: 99%
“…Traditional bulk-loaded synthetic Ca 2+ indicators only delineate the soma and largest processes of the astrocyte ( Reeves et al 2011 ; Leybaert and Sanderson 2012 ). However, astrocyte–neuron communication does not necessarily involve Ca 2+ signals in the astrocytic soma, but may occur in processes and endfeet ( Panatier et al 2011 ; Szokol et al 2015 ). Improved imaging techniques and the development of genetically encoded Ca 2+ indicators now allow us to assess focal and small-scale Ca 2+ transients in these subcellular compartments ( Kanemaru et al 2014 ; Srinivasan et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%